(untitled) (Research, Society and Development, 2024)
Tax planning is increasingly used as a tool for tax optimization and reduction of operational costs in companies, but it has faced challenges within the Brazilian legal system. By analyzing the stance of the Administrative Council of Tax Appeals (CARF), one can observe the use of this theory to define the (il)legality of tax planning and the integrity of corporate reorganizations. The objective of the present study is to analyze the application of this theory as a condition for the validity of taxpayers’ planning within the scope of the Administrative Council of Tax Appeals (CARF), as well as to take a position regarding the application of the Business Purpose Theory in the Brazilian legal system. Thus, this article aims to analyze the evolution of the mentioned theory, as well as outline its application in the Brazilian legal system, in order to conclude on the use of the Business Purpose Theory as a limit for conducting Tax Planning, with the objective of providing a better understanding of the legality of legal transactions that aim solely at tax savings. To this end, its analysis is based on bibliographic and jurisprudential research within the administrative and judicial scope.